1996
DOI: 10.1063/1.360853
|View full text |Cite
|
Sign up to set email alerts
|

Initial stage of native oxide growth on hydrogen terminated silicon (111) surfaces

Abstract: We investigated the initial stage of native oxide growth on an atomically flat hydrogen terminated silicon (Si) (111) surface by immersion in pure water using Fourier transformed infrared attenuated total reflection spectroscopy and reflection absorption spectroscopy. There is a sharp absorption peak at 2083 cm−1 arising from silicon monohydrides at surface terraces, this peak decreases and broadens with immersion time and seems to separate into two components. This broadening is considered to reflect the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 16 publications
(29 reference statements)
3
45
0
Order By: Relevance
“…The latter value is close to the experimental value of 2250 cm -1 attributed to ν s (Si-H) with the three back bonds oxidized. 15 The calculated value is 37 cm -1 lower that the experimental value. However, we note that in our calculations only one of the four silicon atoms in the (2 × 2) unit cell has been oxidized (see Figure 2c).…”
Section: Resultsmentioning
confidence: 82%
“…The latter value is close to the experimental value of 2250 cm -1 attributed to ν s (Si-H) with the three back bonds oxidized. 15 The calculated value is 37 cm -1 lower that the experimental value. However, we note that in our calculations only one of the four silicon atoms in the (2 × 2) unit cell has been oxidized (see Figure 2c).…”
Section: Resultsmentioning
confidence: 82%
“…It is important to keep in mind, that in XPS, the photoelectrons are collected from a so called escape depth, which varies with the electron energy. For our experimental conditions, the escape depth may be estimated as (15-30) A, or (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) monolayers of silicon in the (100) crystallographic direction [8]. Thus, atomic concentrations presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to this study, a silicon surface polished by colloidal silica is predominately covered by dihydride species, a significant fraction of which is backbonded to oxygen. Such a chemical structure of the silicon top layer resembles an early stage of silicon native oxidation [11,19,20].…”
Section: Thickness Of Silicon Oxide Layermentioning
confidence: 99%
“…27,28 Furthermore, the mechanism of oxidation on Si-H surfaces has been proposed to involve insertion of O into the Si-Si backbonds. [29][30][31] Previous core photoelectron spectroscopic studies of the Si(111)/SiO 2 interface have shown that Si(I) and Si(III) are more abundant than Si 2+ because disrupting an atomically flat (111) surface through layer-by-layer oxidation will cleave either 1 or 3 Si tetrahedral bonds. 6,14,[32][33][34][35] Two Si bonds will be cleaved only at step edges and etch defects, which are a minor component of Si(111) surfaces prepared in this manner.…”
Section: Discussionmentioning
confidence: 99%